Tailored Modulation of Cellular Pro-inflammatory Responses With Disaccharide Lipid A Mimetics - Heine, Holger; Adanitsch, Florian; Peternelj, Tina Tinkara; Haegman, Mira; Kasper, Christoph; Ittig, Simon; Beyaert, Rudi; Jerala, Roman; Zamyatina, Alla (Frontiers in Immunology, 2021)
Pro-inflammatory signaling mediated by TLR4/MD-2 complex plays crucial role in the instantaneous protection against infectious challenge and largely contributes to recovery from Gram-negative infection. Activation of TLR4 also boosts the adaptive immunity which is implemented in the development of vaccine adjuvants by application of minimally toxic TLR4 activating ligands. The modulation of pro-inflammatory responses via TLR4 signaling pathway was found beneficial for management of acute and chronic inflammatory disorders including asthma, allergy, arthritis, Alzheimer disease pathology, sepsis, and cancer. The TLR4/MD-2 complex can recognize the terminal motif of Gram-negative bacterial lipopolysaccharide – a glycophospholipid lipid A. Although immense progress in understanding the molecular basis of LPS-induced TLR4-mediated signaling has been achieved, gradual and predictable TLR4 activation by structurally defined ligands has not yet been attained. We report on controllable modulation of cellular pro-inflammatory responses by application of novel synthetic glycolipids - disaccharide-based lipid A mimetics (DLAMs) having picomolar affinity for TLR4/MD-2. Using crystal structure inspired design we have developed endotoxin mimetics where the inherently flexible β(1→6)-linked diglucosamine backbone of lipid A is replaced by a conformationally restricted α,α-(1↔1)-linked disaccharide scaffold. The tertiary structure of the disaccharide skeleton of DLAMs mirrors the 3-dimensional shape of TLR4/MD-2 bound E. coli lipid A. Due to exceptional conformational rigidity of the sugar scaffold, the specific 3D organization of DLAM must be preserved upon interaction with proteins. These structural factors along with specific acylation and phosphorylation pattern can ensure picomolar affinity for TLR4 and permit efficient dimerization of TLR4/MD-2/DLAM complexes. Since the binding pose of lipid A in the binding pocket of MD-2 (+/-180°) is crucial for the expression of biological activity, the chemical structure of DLAMs was designed to permit a predefined binding orientation in the binding groove of MD-2, which ensured tailored and species-independent (human and mice) TLR4 activation. Manipulating phosphorylation and acylation pattern at the sugar moiety facing secondary dimerization interface allowed for adjustable modulation of the TLR4-mediated signaling. Tailored modulation of cellular pro-inflammatory responses by distinct modifications of the molecular structure of DLAMs was attained in primary human and mouse immune cells, lung epithelial cells and TLR4 transfected HEK293 cells.